2008
DOI: 10.1177/0960327108092289
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glucagon on amitriptyline-induced cardiovascular toxicity in rats

Abstract: The aim of this study was to investigate the effect of glucagon on cardiovascular parameters in anesthetized rat model of tricyclic antidepressant overdose. Toxicity was induced by infusion of amitriptyline 0.94 mg/kg/min until a 40–45% of reduction in mean arterial pressure was observed. Amitriptyline infusion rats were then randomized into three groups. Control group of rats (group 1) received a bolus of 5% dextrose followed by the continuous infusion of dextrose, whereas treatment groups received 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 15 publications
(20 reference statements)
1
16
1
Order By: Relevance
“…These results confirm the previous reports describing the positive chronotropic and inotropic effects of glucagon on the myocardial tissue [1, 29, 30]. In addition, glucagon pretreatment caused a decrease in coronary perfusion pressure as a consequence of vasodilatation of the coronary vessels.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results confirm the previous reports describing the positive chronotropic and inotropic effects of glucagon on the myocardial tissue [1, 29, 30]. In addition, glucagon pretreatment caused a decrease in coronary perfusion pressure as a consequence of vasodilatation of the coronary vessels.…”
Section: Discussionsupporting
confidence: 92%
“…Glucagon is an endogenous polypeptide hormone that exerts positive inotropic and chronotropic effects on the myocardial tissue [29, 30]. Cardiac effects of glucagon are considered to be resultant from stimulation of glucagon receptors associated with Gs protein, which cause adenylyl cyclase (AC) activation and the consequent increase of 3′,5′,-cyclic adenosine monophosphate (cAMP) production [31].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, amitriptyline infusion did not cause any significant change in HR. We did not observe any significant changes in our previous studies (Kalkan et al, 2004;Kaplan et al, 2008). The reason for this is difficult to explain, but this could be due to the insensitivity of the Wistar rats to anticholinergic effects.…”
Section: Drug and Chemical Toxicology Downloaded From Informahealthcacontrasting
confidence: 64%
“…The use of vasopressor agents, such as norepinephrine, phenylephrine, or vasopressor doses of dopamine, may also be considered (Benowitz, 2004;Liebelt and Francis, 2002;Thanacoody and Thomas, 2005). Recent experimental studies have shown that many agents, such as L-NAME, a nitric-oxide synthase inhibitor, selective adenosine A 1 and A 2a receptor antagonists, and glucagon, are effective in reversing TCA-induced hypotension (Kalkan et al, 2004;Pentel et al, 1996;Tuncok et al, 2002;Kaplan et al, 2008). There are case reports suggesting the beneficial effects of vasopressin and glucagon in TCA overdose (Sensky and Olczak, 1999;Downes, 2003;Barry et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The glucagon is an endogenous polypeptide hormone that exerts both positive inotropic and the chronotropic effects on the myocardial tissue [23, 24]. The investigations of the glucagon influence on the transport of the radiolabeled histamine in the isolated guinea pig heart demonstrated the elevation of the histamine transport in the presence of glucagon [25, 26].…”
Section: Introductionmentioning
confidence: 99%